2003
DOI: 10.1046/j.1365-2583.2003.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in mitochondrial DNA and gene transcription in freezing‐tolerant larvae of Eurosta solidaginis (Diptera: Tephritidae) and Gynaephora groenlandica (Lepidoptera: Lymantriidae)

Abstract: Respiration, mitochondrial (mt)DNA content, and mitochondrial-specific RNA expression in fat body cells from active and cold-adapted larvae of the goldenrod gall fly, Eurosta solidaginis, and the Arctic woolly bear caterpillar, Gynaephora groenlandica, were compared. Reduced amounts of mtDNA were observed in cold-adapted larvae of both E. solidaginis and G. groenlandica collected in fall or winter, compared with summer-collected larvae. mtDNA increased to levels similar to those of summer-collected larvae afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…A more recent study used molecular techniques (densitometry of dots blots and Northern blots) to analyse mitochondrial copy number and gene transcription in larvae of E. solidaginis and G. groenlandica to assess whether mitochondrial degradation is an adaptive physiological response to cold (Levin et al 2003). This study concluded that although mitochondrial (mt) DNA content was reduced in cold adapted larvae, stable mitochondrial-specific mRNAs were preserved over winter in fat body cells of both E. solidaginis and G. groenlandica.…”
Section: Mitochondrial Degradationmentioning
confidence: 99%
“…A more recent study used molecular techniques (densitometry of dots blots and Northern blots) to analyse mitochondrial copy number and gene transcription in larvae of E. solidaginis and G. groenlandica to assess whether mitochondrial degradation is an adaptive physiological response to cold (Levin et al 2003). This study concluded that although mitochondrial (mt) DNA content was reduced in cold adapted larvae, stable mitochondrial-specific mRNAs were preserved over winter in fat body cells of both E. solidaginis and G. groenlandica.…”
Section: Mitochondrial Degradationmentioning
confidence: 99%
“…Cold acclimation Mammals Transcriptional activation by PGC-1 and NRFs (45) Increased mitochondrial biogenesis Uncoupling to increase proton leak by UCP1 (53) Generation of heat Fish Translational activation or enhanced protein stability (46) Increased mitochondrial enzyme levels Remodeling membrane composition and increased proton leak (48)(49)(50)52) Enhanced enzyme activity Insects Reduction of mtDNA (47) Reduced mitochondrial respiration…”
Section: Regulatory Mechanisms Mitochondrial Responsementioning
confidence: 99%
“…Work on this species and on the gall fly Eurosta solidaginis, using molecular assays for mitochondrial nucleic acids, confirmed the winter losses and suggested that mitochondrial proteins can be regenerated rapidly in spring from stable RNAs that are stored during the winter (Levin et al, 2003).…”
Section: Seasonal Changes In Mitochondriamentioning
confidence: 79%